Performa Struktur Kolom Pasca Perkuatan Dengan Metode Concrete Jacketing Bertulangan Bambu - Hadi Surya Wibawanto Sunarwadi (Universitas Islam 45, 2021)
Columns are the most important element in a structure. Indonesian concrete regulations SNI 2847-2013 states that columns are elements that receive a minimum axial and bending loads of 0.1 Pu. Column damage can occur due to overloading damage, poor detailing in design, poor construction, etc. However, the most frequent damage is post-earthquake damage. The easiest reinforcement is the concrete jacketing method. The reinforcement material used in this research is bamboo. The test was done using the Quasi Static Loading Test method with lateral loads according to the displacement control and constant axial load. The results showed that the reinforcement by concrete jacketing from the initial dimensions of 15x15x90 cm to 21x21x90 cm showed the increase of lateral capacity, ductility, stiffness, and energy dissipation. In addition, it can be seen that the effect of reinforcement on both damaged and undamaged columns is less significant, which means that reinforcement can restore the initial capacity of existing test specimens to exceed 100%.